2002
DOI: 10.1038/sj.bjp.0704656
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of IL‐13 synthesis in human lymphocytes: implications for asthma therapy

Abstract: 1 IL-13 is an important mediator in in¯ammatory diseases such as asthma. IL-13 is mainly produced by T cells. However, signalling pathways leading to induction of this cytokine are not wellcharacterized. We analysed the regulation of IL-13 in human peripheral blood mononuclear cells and CD4 + T cells. 2 Cyclosporine (CsA) and FK-506 inhibited IL-13 synthesis, when cells were stimulated by TPA/ ionomycin. However, stimulation by a-CD3/a-CD28 led to an enhanced IL-13 synthesis. 3 NF-kB inhibitor N-tosyl-L-lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 72 publications
6
35
2
1
Order By: Relevance
“…The expression of Th2 cytokines genes has previously been reported to be blocked by p38 MAPK inhibition (25)(26)(27)(28)(29)(30). In murine T cells, both the TCR CD3 and coreceptor CD28 need to be ligated for maximal duration of p38 MAPK activation (31), and this is confirmed in our studies.…”
Section: Discussionsupporting
confidence: 86%
“…The expression of Th2 cytokines genes has previously been reported to be blocked by p38 MAPK inhibition (25)(26)(27)(28)(29)(30). In murine T cells, both the TCR CD3 and coreceptor CD28 need to be ligated for maximal duration of p38 MAPK activation (31), and this is confirmed in our studies.…”
Section: Discussionsupporting
confidence: 86%
“…Actin primers and probes have been described previously (32). Human Foxp3 primers and probes were purchased as an Assay-On-Demand from Applied Biosystems.…”
Section: Quantitative Pcr Of Foxp3 Mrnamentioning
confidence: 99%
“…TCR engagement in naive CD4 ϩ T cells has been shown to produce IL-4 via activation of ERK (21). U0126 has been shown to inhibit the IL-13 synthesis from 12-O-tetradecanoylphorbol-13-acetate/ionomycin-activated human T cells via ERK inhibition (22). It has been reported that by lowering the ratio of ERK to p38 MAPK activation, dendritic cells could be raised with Th1-polarizing capacity, indicating that ERK signaling pathway in the APCs may promote the initial commitment of naive Th cells toward Th2 phenotype (23).…”
Section: Discussionmentioning
confidence: 99%